Decreased Palpebral Fissure in Patients with Parkinson's Disease. Issue 1 (24th March 2016) - Sanchez Abraham, Marina; Gomez Arevalo, Gonzalo; Garcia, Silvia S.; Mizraji, Gabriel; Chade, Anabel; Gershanik, Oscar
Abstract: Background: The diagnosis of Parkinson's disease (PD) is based exclusively on clinical criteria established by the Queen Square Brain Bank. On occasion, these clinical symptoms may be subtle and inconclusive; therefore, it becomes necessary to appeal to contributory criteria to establish a correct diagnosis. The authors propose the observation of palpebral fissure (PF) asymmetry as an additional criterion for the diagnosis of PD. Objectives: The objectives of this study were to determine whether decreased PF (DPF) is more prevalent in patients with PD than in the general population and whether DPF in PD coincides with the side of onset of parkinsonian symptomatology. Methods: In total, 112 consecutive patients with a diagnosis of PD and 112 control participants without PD were selected between April and June 2014. At the office visit, it was established through clinical observation whether DPF was present. In patients with PD, it was determined whether the DPF was consistent with the side of onset of parkinsonian symptomatology. Results: Of 112 patients with PD, 39 (35%) had DPF clinically evident DPF, and, in 34 (87%), the DPF was consistent with the laterality of parkinsonian signs. In the control group, only 12% (14 of 112 controls) had PF asymmetry. The difference in prevalence of DPF between these groups was statistically significant ( P < 0.0001), with an odds ratio of 3.7 (95% confidence interval, 1.8–7.3). Twenty‐eight of the 39 patients with PD who had PF asymmetry were treated with levodopa. Conclusions: Although the data are purely observational, it may be concluded that DPF coincidental with the side of initial parkinsonian symptomatology in patients with probable PD is an additional sign worth considering.